Microbial, enzymatic and physico-chemical quality changes during storage of tomatoes (Solanum lycopersicum) harvested from polyhouse vs. open conditions - GARG, NEELIMA; SINGH, V K; PRITI, PRITI; YADAV, KAUSHLESH K; KUMAR, SANJAY; YADAV, PREETI (The Indian Journal of Agricultural Sciences, 2017)
Protected cultivation of vegetables is gaining importance owing to its perpetual demand throughout the year. Effect of cultivating tomato (Solanum lycopersicum L.) cultivar Himsona under polyhouse conditions on the microbial and physico-chemical quality and enzymatic behavuior was studied and compared with open conditions at the time of harvesting and during storage under ambient conditions. Study on microflora of tomato fruits grown under open and polyhouse conditions revealed presence of fungi, viz. Acremonium sp., Rhizopus sp. and Aspergillus sp. in fruits harvested from open while fruits under polyhouse condition contained fungus Acremonium sp. only. Spoilage started in open fruits from 6th day of storage under ambient conditions due to dominance of Rhizopus sp. The bacterial counts on polyhouse grown fruits were about 100 times less than open cultivated fruits. Polygalacturonase activity was initially higher (0.139 U/ml) in open conditions compared to polyhouse condition (0.074 U/ml). It increased sharply to 1.50 U/ml on 4th day of storage in open conditions compared to slow increase under polyhouse condition (0.140 U/ml). On 6th day senescence started as evidenced by decrease in polygalacturaonase activity and increase in surface fungal counts in fruits from open conditions, which finally spoiled on 8th day due to dominance of Rhizopus sp. The fruits from polyhouse were still marketable at the end of 8th day. The study proves that tomato fruits grown in polyhouse are microbiologically safer and have better shelf life.